2018
DOI: 10.1017/s0025315418000620
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of the crabHepatus pudibundus(Herbst, 1785) (Decapoda, Aethridae) on the southern coast of São Paulo state, Brazil

Abstract: The present study investigated the population dynamics of Hepatus pudibundus in the Cananéia region, in southern São Paulo state, Brazil, focusing on population structure, growth parameters, longevity, sex ratio, reproduction and recruitment juvenile period. Sampling was performed monthly at seven stations from July 2012 to June 2014, using a shrimp fishing boat. A total of 1650 specimens were collected: 551 males and 1099 females. The males were larger than females. Reproductive females were captured througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…(2014) in Ubatuba and by Miazaki et al. (2019) in the region of Cananéia have shown that H. pudibundus recruitment occurs in the winter. Altogether, these and previous results indicate that this is the recruitment pattern along the coast of São Paulo, and that it increases the reproductive success and leads to a high adaptive value (fitness) in this region.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…(2014) in Ubatuba and by Miazaki et al. (2019) in the region of Cananéia have shown that H. pudibundus recruitment occurs in the winter. Altogether, these and previous results indicate that this is the recruitment pattern along the coast of São Paulo, and that it increases the reproductive success and leads to a high adaptive value (fitness) in this region.…”
Section: Discussionmentioning
confidence: 90%
“…The higher abundance of adult females compared to adult males in the two periods can be explained by sex-specific dispersal, migration, mortality, and growth rates, corroborating with Jesse and Stotz (2002) and Miazaki et al (2019). Females naturally prefer sheltered areas or strategic locations to avoid conflict, increase protection against predators, and favor egg release (Mantelatto, 2000).…”
Section: Likewise Juveniles Of Other Brachyurans Such As the Swimminmentioning
confidence: 82%
“…Sexual dimorphism with larger males than females seems to be a common pattern for crustaceans, including brachyurans and crayfishes (Miazaki et al ., 2019; Sousa et al ., 2019; Bernardo et al ., 2020; Hamasaki et al ., 2020). According to Hartnoll (1969), males are larger because they tend to protect pre- and post-moulting females with the copulatory embrace, representing an adaptation to ensure reproductive success.…”
Section: Discussionmentioning
confidence: 99%
“…When analysing L. emarginata and other Majoidea as Chionoecetes opilio and Maja squinado (Herbst, 1788), it has been found that OFs can also copulate, since their gonads are already developed and they can store new sperm masses, with females being able to spawn up to four times in a row (Hinsch, 1968; Elner & Beninger, 1995; González-Gurriarán et al ., 1998). The same pattern was found in Cananéia for this species (Gonçalves et al ., 2017), with continuous reproduction being a common feature of tropical and subtropical marine brachyurans such as: L. spinosa (Braga et al ., 2007), Persephona mediterranea (Herbst, 1794) (Bertini et al ., 2010 b ), C. ornatus (Andrade et al ., 2014), Arenaeus cribarius (Lamarck, 1818) (Silva et al ., 2018) and H. pudibundus (Miazaki et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, a pooled VBGF was estimated. Maximum longevity (T max ) was calculated by the inverted von Bertalanffy equation, using 99 % of the asymptotic size as recommended by D'Incao and Fonseca 2000, and recently supported by investigations on brachyurans (Miazaki et al, 2019;Gonçalves et al, 2020). Average maximum longevity was estimated by 95 % of the largest animals (Taylor, 1965).…”
Section: Growth and Mortality Of Rhithropanopeus Harrisiimentioning
confidence: 99%